2017
DOI: 10.3389/fpsyt.2017.00175
|View full text |Cite
|
Sign up to set email alerts
|

Common Marmosets: A Potential Translational Animal Model of Juvenile Depression

Abstract: Major depression is a psychiatric disorder with high prevalence in the general population, with increasing expression in adolescence, about 14% in young people. Frequently, it presents as a chronic condition, showing no remission even after several pharmacological treatments and persisting in adult life. Therefore, distinct protocols and animal models have been developed to increase the understanding of this disease or search for new therapies. To this end, this study investigated the effects of chronic social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 114 publications
0
27
0
Order By: Relevance
“…Some studies with animal models of depression, rodents and non-human primates, observed positive antidepressant effects with the use of ayahuasca or its specific components ( 90 – 92 ). Using the recently validated translational animal model of depression ( 93 ), young marmosets ( Callithrix jacchus ) that showed hypocortisolemia, were treated with nortriptyline during 7 days, a tricyclic antidepressant, or with a single dose of ayahuasca. It was observed that ayahuasca increased fecal cortisol levels until 48 h after it ingestion, and presented more notable antidepressant effects than nortriptyline, since it reverted depressive-like behaviors and regulated cortisol levels faster and longer, when compared with nortriptyline ( 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies with animal models of depression, rodents and non-human primates, observed positive antidepressant effects with the use of ayahuasca or its specific components ( 90 – 92 ). Using the recently validated translational animal model of depression ( 93 ), young marmosets ( Callithrix jacchus ) that showed hypocortisolemia, were treated with nortriptyline during 7 days, a tricyclic antidepressant, or with a single dose of ayahuasca. It was observed that ayahuasca increased fecal cortisol levels until 48 h after it ingestion, and presented more notable antidepressant effects than nortriptyline, since it reverted depressive-like behaviors and regulated cortisol levels faster and longer, when compared with nortriptyline ( 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for ayahuasca’s rapid antidepressant action in adult patients raises the question of whether it might also be effective in other age groups susceptible to depression, such as adolescents. Due to this possibility and to the lack of animal studies on ayahuasca in juvenile depression, this study evaluated the acute antidepressant effects of ayahuasca on body weight and physiological (fecal cortisol) and behavioral parameters in a recently developed juvenile model of depression that involves the induction of a depressive-like state in the common marmoset ( Callithrix jacchus ) through chronic social isolation 16…”
Section: Introductionmentioning
confidence: 99%
“…Some studies with animal models of depression, rodents and non-human primates, observed positive antidepressant effects with the use of ayahuasca or its specific components (81, 82, 83). Using the recently validated translational animal model of depression (84), young marmosets ( Callithrix jacchus ) were treated with nortriptyline during 7 days, a tricyclic antidepressant, or with a single dose of ayahuasca. It was observed that ayahuasca increased fecal cortisol levels until 48 hours after it ingestion and presented more notable antidepressant effects than nortriptyline, since it reverted depressive-like behaviors and regulated cortisol levels faster and during more time (83).…”
Section: Discussionmentioning
confidence: 99%